2014
DOI: 10.1097/mao.0000000000000464
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Preoperative Characteristics of Chronic Otitis Media in Down and Non-Down Syndrome

Abstract: Frequent draining ear and extremely immature mastoid pneumatization, regardless of the presence or absence of a past history of tympanostomy tube insertion, were clinically important characteristics of COM in patients with Down syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…[8] Shinnabe et al found that persistent otorrhea was significantly more frequent in DS patients than non-DS prior to tympanoplasty. [6] Manickam et al followed a group of DS patients for 15 years and found that chronic otitis media and indications for pressure equalization tube placement are still prevalent as DS children age. [4] These studies support our findings that DS is over-represented in the upper airway and otologic procedures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8] Shinnabe et al found that persistent otorrhea was significantly more frequent in DS patients than non-DS prior to tympanoplasty. [6] Manickam et al followed a group of DS patients for 15 years and found that chronic otitis media and indications for pressure equalization tube placement are still prevalent as DS children age. [4] These studies support our findings that DS is over-represented in the upper airway and otologic procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the current literature describes surgical outcomes of DS patients undergoing more common otolaryngologic procedures such as adenoidectomy, tonsillectomy, and tympanostomy tube placement. [3-6] Surgical intervention in DS patients is complicated by multiple systemic comorbidities and certain anesthetic considerations like atlantoaxial instability. [7, 8] There are only a few studies looking at the treatment of DS patients from a broad otolaryngologic perspective.…”
Section: Introductionmentioning
confidence: 99%
“…Poor mastoid pneumatization is characteristic in patients with Down syndrome, regardless of the presence or absence of a history of TT insertion. 170 Similarly, children with CP, especially bilateral CP, had smaller mastoid areas than did subjects with OME. Srzentić et al 171 measured the mastoid size in children with CP and found that the lowest pneumatization was found in bilateral CP.…”
Section: Mastoid Anatomymentioning
confidence: 99%
“…There is little evidence regarding the effectiveness of these management strategies in children with DS, with each having associated risks specific to children with DS. For example, grommet surgery may be difficult due to a narrow ear canal and children with DS are at increased risk of grommet associated ear discharge and eardrum perforation . Air conduction hearing aids often do not fit well or exacerbate ear infections.…”
Section: Introductionmentioning
confidence: 99%
“…For example, grommet surgery may be difficult due to a narrow ear canal and children with DS are at increased risk of grommet associated ear discharge and eardrum perforation. 3 Air conduction hearing aids often do not fit well or exacerbate ear infections. Consequently, there is a need for further research regarding the effectiveness, acceptability and utilisation of management strategies for hearing loss associated with persistent OME, in children and young people with DS.…”
mentioning
confidence: 99%